2018
DOI: 10.1049/iet-ifs.2017.0257
|View full text |Cite
|
Sign up to set email alerts
|

Information security collaboration formation in organisations

Abstract: Collaboration between employees in the domain of information security efficiently mitigates the effect of information security attacks on organisations. Collaboration means working together to do or to fulfil a shared goal, the target of which in this paper is the protection of the information assets in organisations. Information Security Collaboration (ISC) aims to aggregate the employees' contribution against information security threats. This study clarifies how ISC is to be developed and how it helps to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Bauer et al (2017) similarly concluded that IS intervention influenced users' neutralization behaviors and improved IS knowledge and responsibilities. Finally, experience effectively increased awareness of potential IS threats and positively influenced attitudes about policy compliance, in line with other studies (e.g., Safa et al, 2017;Tatu et al, 2018).…”
Section: Zhu Et Al (2023)supporting
confidence: 86%
See 3 more Smart Citations
“…Bauer et al (2017) similarly concluded that IS intervention influenced users' neutralization behaviors and improved IS knowledge and responsibilities. Finally, experience effectively increased awareness of potential IS threats and positively influenced attitudes about policy compliance, in line with other studies (e.g., Safa et al, 2017;Tatu et al, 2018).…”
Section: Zhu Et Al (2023)supporting
confidence: 86%
“…Thus, an individual can become more proficient after expending the effort and time to gain experience in a field and more prone to handle problems by looking for effective solutions (Blythe & Coventry, 2018;Liang et al, 2022;Tatu et al, 2018). In IS, experience increases user awareness of potential threats (Tatu et al, 2018), an important aspect of a secure information environment (Safa et al, 2017). This informed the seventh hypothesis:…”
Section: Information Security Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Theory of planned behavior The theory says that the attitude toward the behavior and subjective norms form an individual's behavioral intentions and actions 3,30,31 Neutralization theory Neutralization theory is a psychological method for people to turn off "inner resistance" when they perform or are about to perform something that they perceive as ethically wrong 3 Learning theory Learning theory explains how information is understood, treated, and retained by participants during the learning process 3 Protection motivation theory The protection motivation theory argues that people guard themselves based on four factors: (a) the perceived severity of an event and the occurrence; (b) vulnerability of the person; (c) the person's ability for the preventive behavior; and (d) believe in his ability to protect 3,30 General deterence theory General Deterrence is a plan designed to deter an opponent from taking actions which are not yet initiated or in another case to prevent people from performing actions that opponent wants them to do 30 Social learning theory Social Learning Theory asserts that people acquire knowledge from one another, via perception, memory, and modeling 30 Social bonding theory Social bond theory is used to explain social issues. Factors of social bonding comprise an attachment to families, devotion to social norms and institutions, engagement in activities, and the faith that these things are essential [30][31][32] General strains theory Innovation happens when community stresses culturally acceptable goals but at the same time provides insufficient opportunity to accomplish these goals with the legal institutionalized means. People finding themselves in financial strain may find a solution of crime in order to achieve goals 30 Organizational injustice If the leaders of the institution are authoritarian, their effort to solve the problems may be ineffective due to many reasons and may increase organizational stress and efficiency of the employees.…”
Section: Theory Explanation Referencesmentioning
confidence: 99%